Allostatic Load, Income, and Race Among Black and White Men in the United States. Issue 2 (April 2022) - Tavares, Carlos D.; Bell, Caryn N.; Zare, Hossein; Hudson, Darrell; Thorpe, Roland J.
Research indicates that income is significantly associated with allostatic load (AL) and that this association may differ between White and Black Americans. Most existing income–AL link work focuses on women and less is known about this association among men. Using data from the National Health and Nutrition Examination Survey (NHANES), we examined whether race moderates the association between income and AL among Black and White men in the United States ( n = 5, 685). We find that, regardless of income levels, Black men have significantly higher prevalence of being in the high-AL group compared with high-income White men. Our findings suggest that Black men do not receive the same health benefits for increased income relative to their White counterparts.